THE ARISTOCRAT BECOMES A COURTIER… FEATURES OF EUROPEAN ARISTOCRATIC CULTURE IN THE 17th CENTURY - Hanovs, Deniss (Via Latgalica, 2008)
As John Adamson outlined in his voluminous comparative analysis of European court culture, „in the period between 1500 and 1750 a „Versailles model” of a court as a self-sufficient, situated in a free space, architectonically harmonious city-residency remote from the capital city, where the king’s household and administration was located, was an exception.” The Versailles conception and „model” both architectonically and in terms of practical functioning of the court was spread and secured in the 18th century, developing into a model of absolutism which was imitated to different extents. The spectrum of the adoption of the court of Louis XIV by material and intellectual culture reached from the grand ensembles of palaces of Carskoye Selo in Peterhof, Russia, Drottningholm in Sweden and Sanssouci in Germany to several small residences of the German princes’ realms in Weimar, Hanover, and elsewhere in Europe. Analyzing the works of several researchers about the transformation of the French aristocracy into court society, a common conclusion is the assurance of the symbolic autocratic power by Louis XIV to the detriment of the economic and political independence of the aristocracy. In this context, A. de Tocqueville points at the forfeiture of the power of the French aristocracy and its influence and a simultaneous self-isolation of the group, which he defines as a „caste with ideas, habits and barriers that they created in the nation.” Modern research, when revisiting the methods of the resarch on the aristocracy and when expanding the choice of sources, is still occupied with the problem defined in the beginning of the 19th century by A. de Tocqueville: The aristocracy lost its power and influence, and by the end of the 18th century also its economic basis for its dominance in French society. John Levron defines courtiers as functional mediators between the governor and society, calling them a „screen”.1 In turn, Ellery Schalk stated that in the time of Louis XIV the aristocracy was going through an elite identity crisis, when alongside the old aristocracy involved in military professions (noblesse d’épée), the governor allowed a new, so-called administrative aristocracy (noblesse de robe) to hold major positions and titles of honour. Along with the transformation of the traditional aristocratic hierarchy formed in the early Middle Ages, which John Lough described as an anachronism already back in the 17th century, also the status of governor and its symbolic place in the aristocratic hierarchy changed. It shall be noted that it is the question of a governor’s role in the political culture of absolutism by which the ideas of many researches can be distinguished. Norbert Elias thinks that an absolute monarch was a head of a family, which included the whole state and thereby turned into a governor’s „household”. Timothy Blanning, on the other hand, thinks that the court culture of Louis XIV was the expression of the governor’s insecurity and fears. This is a view which the researcher seems to derive from the traumatic experience of the Fronde (the aristocrats’ uprising against the mother of Louis XIV, regent Anna of Austria), which the culturologist K. Hofmane interpreted from a psychoanalytical point of view and defined Louis XIV as a conqueror of chaos and a despotic governor. In the wide spectrum of opinions, it is not the governor’s political principles which are postulated as a unifying element, but scenarios of the representation of power, their aims and various tools that are combined in the concept of court culture. N. Elias names symbolic activities in the court etiquette as the manifestation of power relations, whereas M. Yampolsky identifies a symbolic withdrawal of a governor’s body from the „circulation in society”, when a governor starts to represent himself, thereby alienating himself from society. George Gooch in this way reprimanded Louis XV as he thought this development would deprive the royal representation from the sacred. In turn, Jonathan Dewald in his famous work „European Aristocracy” noted that Louis XIV was not the first to use the phenomenon of the court for securing the personal authority of a governor, and refers to the courts during the late period of the Italian Renaissance as predecessors of French court culture. What role did the monarch’s closest „viewers” – the courtiers – play in this? K. Hofmane by means of comparison with the ancient Greek mythical monster Gorgon comes to conclusion that the court had to provide prey for the Gorgon (the king), who is both scared and fascinated by the terrific sight (of power and glory). The perception of the court as a collective observer implies the presence of the observed and worshiped object, the king. The public life of Louis XIV, which was subjected to the complicated etiquette, provided for the hierarchical access to the king’s public body. Let’s remember the „Memoirs” of Duc de Saint-Simon that gives a detailed description of the symbolic privileges granted to the courtiers, which along the material gifts (pensions, concessions and land plots) were tools for the formation of the identity and the status of a new aristocrat/courtier – along with the right to touch the king’s belongings, his attire, etc. The basis for securing the structure of the court’s hierarchy was provided by the governor’s body along the lines mentioned above, which according to the understanding of representation by M. Yampolsky was withdrawn from society and placed within the borders of the ensemble of the Versailles palace. There, by means of several tools, including dramatic works of art, the governor’s body was separated from its symbolic content and hidden behind the algorithms of ritualized activities. Blanning also speaks about a practice of hiding from the surrounding environment, thereby defining court culture as a hiding-place that a governor created around himself. It was possible to look at a governor and thereby be observed by him not only on particular festivals, when a governor was available mostly for court society, but also in different works of visual art, for example, on triumphal archs, in engravings, or during horse-racings.